2011
DOI: 10.1039/c1ob05083d
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid peroxidation vs. isomerization: a biomimetic model of free radical reactivity in the presence of thiols

Abstract: Biomimetic models of free radical-induced transformation of polyunsaturated fatty acids, such as micelles and liposomes, have been used for the study of lipid peroxidation and lipid isomerization. Free radical reactivity of thiol compounds is the common link between the two processes, since lipid peroxidation is inhibited by thiols, due to their H-donation ability, whereas lipid isomerization is catalysed by S-centered radicals. In this paper the two processes are compared for the first time, in solution and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 50 publications
5
33
0
Order By: Relevance
“…This was also in agreement with an in vitro study that investigated the competition between lipid peroxidation and isomerization. Indeed, the major trans isomer of 9c,12c-18:2 formed in liposomes was 9t,12c-18:2 [12]. We detected only this specific isomer in our cohorts but not the 9t,12t-18:2 or 9c,12t-18:2.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This was also in agreement with an in vitro study that investigated the competition between lipid peroxidation and isomerization. Indeed, the major trans isomer of 9c,12c-18:2 formed in liposomes was 9t,12c-18:2 [12]. We detected only this specific isomer in our cohorts but not the 9t,12t-18:2 or 9c,12t-18:2.…”
Section: Discussionmentioning
confidence: 62%
“…Beside, the thiyl radical, it has also been demonstrated that some isomers of trans-arachidonic acid may originate from the NO 2 -mediated AA isomerization in human [14]. An in vitro study has shown the competition between lipid peroxidation and isomerization [12]. This competition could explain, at least in part, why correlations are observed between F 2 -isoPs and 9t-18:1 generated from the high level 9c-18:1 but not with 11t-18:1 derived from the low level 11c-18:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of TWEEN®‐20 concentrations on LA oxidation was determined under the conditions of constant LA and varying TWEEN®‐20 concentrations (Table 2). It should be pointed out that Tween®‐20 alone did not induce lipid peroxidation process in the solutions of LA 23. The solutions were prepared by diluting the original solution with aqueous surfactant solutions in 5.0 mM MES.…”
Section: Resultsmentioning
confidence: 99%
“…One of them is lipid peroxidation [1][2][3] and the second one is the process of geometrical isomerization of naturally occurring cis unsaturated lipids which can be catalyzed by thiyl radicals (RS ) [4][5][6]. It has been shown that one process can be parallel with the occurrence of the other and both lipid hydroperoxides and trans lipids are the resulting products of oxidative free radical conditions [7] (Scheme 1). Investigations of peroxidation and isomerization processes in liposome models were shown to occur by chemical agents, such as the antitumor drug bleomycin, known to form metal complexes, thus producing oxidative stress conditions [8].…”
Section: Introductionmentioning
confidence: 99%